(15x+6y)+(41x+34y)=

Simple and best practice solution for (15x+6y)+(41x+34y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (15x+6y)+(41x+34y)= equation:


Simplifying
(15x + 6y) + (41x + 34y) = 0

Remove parenthesis around (15x + 6y)
15x + 6y + (41x + 34y) = 0

Remove parenthesis around (41x + 34y)
15x + 6y + 41x + 34y = 0

Reorder the terms:
15x + 41x + 6y + 34y = 0

Combine like terms: 15x + 41x = 56x
56x + 6y + 34y = 0

Combine like terms: 6y + 34y = 40y
56x + 40y = 0

Solving
56x + 40y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-40y' to each side of the equation.
56x + 40y + -40y = 0 + -40y

Combine like terms: 40y + -40y = 0
56x + 0 = 0 + -40y
56x = 0 + -40y
Remove the zero:
56x = -40y

Divide each side by '56'.
x = -0.7142857143y

Simplifying
x = -0.7142857143y

See similar equations:

| (68x+70y)+(-30x+45y)= | | Ax-5bx=2b-3a | | (89x+45y)-(5x+34y)= | | 6(2x+3)-(x-4)=x+2 | | 3x+4x+15=120 | | 2x-2y+3z=18 | | 6q-18=18 | | 9x^2+7=2 | | (72x-47y)-(63x+21y)= | | (49x+62y)-(21x-23y)= | | z/3-3=5 | | v-3/5=8.5 | | 1/5a=3.1 | | n/5+11=13 | | (12z^6-32z^6)/4z^2 | | C=400+15n | | (64x+56y)-(7x+38y)= | | 4(4x+14)+9x-17= | | X+7x/4=33 | | (9+3x)-3x= | | 3x-5(x+4)=-(x-7) | | 9(x-7)+14(x+10)= | | 4(2x+12)-6x= | | 7(6x+4)+5x= | | 7(t-3)+7t=7(2t+5)-12 | | 5(2x+6)-20= | | 2x^2-32x-72=0 | | (6x+16)-6= | | (55x+60y)-(10x-22y)= | | 7(5x+12)+13x-12= | | (63x+47y)-(3x-6y)= | | 1.6q-2.5-1.5q=-0.9q-3.3 |

Equations solver categories